1999
DOI: 10.1364/ao.38.007145
|View full text |Cite
|
Sign up to set email alerts
|

Frequency doubling of ultrashort laser pulses in biological tissues

Abstract: Theoretical and experimental studies of second-harmonic generation (SHG) in biological tissues was performed by use of ultrashort laser pulses (<1 ps). A simplified one-dimensional model for the generation and the propagation of frequency-doubled light inside tissue was developed. This model was tested in vitro against measurements of pig and chicken tissue and human tooth. The experimental results indicate that the intensity of SHG varies significantly among tissue types and between test sites in individual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 16 publications
1
25
0
2
Order By: Relevance
“…Collagen fibrils have a triple-helical structure, which is believed to be the origin of its nonlinear optical susceptibility. The SH responses from dentin and collagen are compared in Figure 4c and d. In Figure 4c and d (insets), the sharp rise in SH signal during 820 -828 nm for dentin and 796 -806 nm for collagen indicates either the existence of resonance effects (Campagnola et al, 1999) or fulfillment of phase matching conditions (Kim et al, 1999), as predicted by the one-dimensional SH model (Yariv, 1988). The 2-p auto-fluorescence, on the other hand, stays the same both in spectral profile and signal strength.…”
Section: Harmonic Generation Microscopy Ofmentioning
confidence: 98%
See 1 more Smart Citation
“…Collagen fibrils have a triple-helical structure, which is believed to be the origin of its nonlinear optical susceptibility. The SH responses from dentin and collagen are compared in Figure 4c and d. In Figure 4c and d (insets), the sharp rise in SH signal during 820 -828 nm for dentin and 796 -806 nm for collagen indicates either the existence of resonance effects (Campagnola et al, 1999) or fulfillment of phase matching conditions (Kim et al, 1999), as predicted by the one-dimensional SH model (Yariv, 1988). The 2-p auto-fluorescence, on the other hand, stays the same both in spectral profile and signal strength.…”
Section: Harmonic Generation Microscopy Ofmentioning
confidence: 98%
“…Intense SHG has also long been observed on biological samples that possess the so-called biophotonic structures (Clays et al, 2001). Structural proteins, such as collagen, myosin, and elastin, have been shown to possess large nonlinear optical susceptibility (Kim et al, 1999). The unique structure and composition of enamel and dentin are especially suited for study with harmonic generation microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, ultrashort pulse lasers are capable of eliciting second harmonic signals in tissues without structurally damaging them. Furthermore, it has been reported that sub-picosecond laser pulses generate second harmonic light much more effectively than do longer pulses [5]. Such lasers have been used to generate two-dimensional second harmonic images from several types of animal tissue [6].…”
Section: Introductionmentioning
confidence: 99%
“…They lack inversion symmetry which is a necessary condition for second order nonlinear susceptibility. The second order nonlinearity of the collagen is responsible for generation Of light at twice the excitation frequency (second harmonic generation) when interacting with intense laser pulses [2]- [5]. The development of ultrashort pulse laser technology has made it feasible to analyze harmonic generation in collagen nondestructively.…”
Section: Introductionmentioning
confidence: 99%
“…The development of ultrashort pulse laser technology has made it feasible to analyze harmonic generation in collagen nondestructively. Recently, it was reported that femtosecond laser pulses generate second harmonic light in collagen more effectively without damaging the target tissues than picosecond or nanosecond pulses [5].…”
Section: Introductionmentioning
confidence: 99%